Administrative coercive measures used in the field of construction - A. S. Zubkov (Гуманитарные и юридические исследования)
Introduction. The article studies certain administrative coercive measures used to protect public relations in the field of construction, as well as to identifying the problems of their legal consolidation.Materials and methods. The study is based on an analysis of legislative provisions that determine the procedure for applying administrative coercive measures in the field of construction. The use of the formal legal method made it possible to reveal the content of legal norms devoted to their regulation.Analysis. Administrative and legal protection of public relations in the field of construction implies the need to implement various measures of administrative coercion. The legislation is characterized by the absence of an exhaustive list of such measures. Their content can be judged by analyzing specific articles of various regulations.Results. Administrative coercive measures in the field of construction can be divided into administrative and preventive; administrative and recovery; administrative measures; measures to ensure proceedings in cases of administrative offenses; administrative penalties. The author states the need to normatively consolidate the order of the control (supervisory) body in the field of construction and specify its relationship with the act of control (supervisory) activity. An order from a control (supervisory) body in the field of construction must be considered as an administrative coercive measure applied on the basis of an act of a control (supervisory) body in the event of violations of mandatory requirements being detected during a control (supervisory) event, aimed at suppressing actions (inactions) containing signs of violation mandatory requirements in the field of construction, as well as preventing such violations in the future by taking measures to prevent harm (damage) to public relations in the field of construction. The need to expand the list of administrative penalties contained in the Code of Administrative Offenses of the Russian Federation is substantiated by including a new measure - exclusion from the state register of self-regulatory organizations.